2020
DOI: 10.1177/0957650920967559
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fluid-structure interaction modelling on the stress and fatigue life evaluation of a gas turbine blade

Abstract: A computational method of fluid-structure coupling is implemented to predict the fatigue response of a high-pressure turbine blade. Two coupling levels, herein referred to as a “fully coupled” and “decoupled” methods are implemented to investigate the influence of multi-physics interaction on the 3 D stress state and fatigue response of a turbine blade. In the fully-coupled approach, the solutions of the fluid-flow and the solid-domain finite element problem are obtained concurrently, while in the decoupled ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
1
1
0
1
Order By: Relevance
“…( 9) and ( 10) to conserve the energy balance at the interface. For maximum equivalent stress, similar trend was reported by Ubulom [30] and Moffat and He [31] who studied comparison of FSI for coupled and non-coupled cases for gas turbine. These studies were referred since there was no study found for MFT.…”
Section: Blade Deformation and Equivalent Stresssupporting
confidence: 79%
“…( 9) and ( 10) to conserve the energy balance at the interface. For maximum equivalent stress, similar trend was reported by Ubulom [30] and Moffat and He [31] who studied comparison of FSI for coupled and non-coupled cases for gas turbine. These studies were referred since there was no study found for MFT.…”
Section: Blade Deformation and Equivalent Stresssupporting
confidence: 79%
“…При этом, если исследуются вибрационные явления, то колебания лопатки будут оказывать влияние на поток газа, что и имеется в виду при двустороннем FSI, который среди прочего дает более точные результаты в задачах на исследование усталостной прочности и долговечности [50]. Для турбин использование FSI в расчетах тоже является обычной практикой.…”
Section: использование моделейunclassified
“…For the simulation analysis method for studying the forced vibration of turbine blades, the biggest difference between the unidirectional and two-way FSI simulation analysis methods is that the unidirectional fluid-solid coupling simulation analysis method simplifies the influence of aerodynamic damping on the FEA model, while the two-way FSI simulation analysis method takes this factor into account. 17,18 The most common and simplest way to prevent resonance excitation or determine the resonance speed is to make predictions by drawing a Campbell diagram; that is, resonance occurs when the working frequency and the natural frequency are consistent. Although this method is very useful for simple dynamic structural design, it has serious limitations when studying complex components such as turbocharger turbine blades.…”
Section: Introductionmentioning
confidence: 99%